Characterisation of betalain biosynthesis in Parakeelya flowers identifies the key biosynthetic gene DOD as belonging to an expanded LigB gene family that is conserved in betalain-producing species - Chung, Hsiao-Hang; Schwinn, Kathy E.; Ngo, Hanh M.; Lewis, David H.; Massey, Baxter; Calcott, Kate E.; Crowhurst, Ross; Joyce, Daryl C.; Gould, Kevin S.; Davies, Kevin M.; Harrison, Dion K. (Frontiers in Plant Science, 2015)
Plant betalain pigments are intriguing because they are restricted to the Caryophyllales and are mutually exclusive with the more common anthocyanins. However, betalain biosynthesis is poorly understood compared to that of anthocyanins. In this study, betalain production and betalain-related genes were characterized in Parakeelya mirabilis (Montiaceae). RT-PCR and transcriptomics identified three sequences related to the key biosynthetic enzyme Dopa 4,5-dioxgenase (DOD). In addition to a LigB gene similar to that of non-Caryophyllales species (Class I genes), two other P. mirabilis LigB genes were found (DOD and DOD-like, termed Class II). PmDOD and PmDOD-like had 70% amino acid identity. Only PmDOD was implicated in betalain synthesis based on transient assays of enzyme activity and correlation of transcript abundance to spatio-temporal betalain accumulation. The role of PmDOD-like remains unknown. The striking pigment patterning of the flowers was due to distinct zones of red betacyanin and yellow betaxanthin production. The major betacyanin was the unglycosylated betanidin rather than the commonly found glycosides, an occurrence for which there are a few previous reports. The white petal zones lacked pigment but had DOD activity suggesting alternate regulation of the pathway in this tissue. DOD and DOD-like sequences were also identified in other betalain-producing species but not in examples of anthocyanin-producing Caryophyllales or non-Caryophyllales species. A Class I LigB sequence from the anthocyanin-producing Caryophyllaceae species Dianthus superbus and two DOD-like sequences from the Amaranthaceae species Beta vulgaris and Ptilotus spp. did not show DOD activity in the transient assay. The additional sequences suggests that DOD is part of a larger LigB gene family in betalain-producing Caryophyllales taxa, and the tandem genomic arrangement of two of the three B. vulgaris LigB genes suggests the involvement of duplication in the gene family evolution.